Asuhan Keperawatan Perioperatif pada Adenoma Hipofisis dengan Pendekatan Teori Adaptasi Roy - Hellena Deli; Ratna Sitorus; I Made Kariasa; M.G Enny Mulyatsih (Institut Penelitian Matematika, Komputer, Keperawatan, Pendidikan dan Ekonomi (IPM2KPE), 2023)
This study aims to describe the implementation of nursing care in post-endoscopic transsphenoidal surgery (ETSS) patients with indications of pituitary adenoma. This research method is a case study in post-ETSS patients with Roy's Adaptation theory approach. This study showed that the patient was free of postoperative complications. The patient could mobilize in stages and went home in a condition that he could walk even with assistance. During treatment, the patient's blood sugar levels were controlled, and signs of dehydration were not found. In conclusion, strict control and good postoperative care can prevent the risk of postoperative complications in patients. Keywords: Roy Adaptation, Pituitary Adenoma, ETSS